A Note on Weak Separability - Murphy, F. P. (Review of Economic Studies, 1981)
Journal Article A Note on Weak Separability Get access F. P. Murphy F. P. Murphy Trinity College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 4, October 1981, Pages 671–672, https://doi.org/10.2307/2297209 Published: 01 October 1981 Article history Received: 01 August 1980 Accepted: 01 July 1981 Published: 01 October 1981